Video Based Learning as a Media for Teaching English during Pandemic Covid-19 - Prayudha S., Joko (Faculty of Tarbiyah and Teacher Training, IAIN Jember, 2021)
The COVID-19 pandemic has stopped face-to-face learning in schools and switched to using online learning. This study aims to find out the use of video based learning in teaching English in schools during the COVID-19 pandemic. This study used the literature method by collecting and conducting in-depth literature studies. In various studies they were stated that learning by videos have been proven to be able to help teachers and students effectively in encouraging the development of new strategy in the classroom. The result of the study shows that the use of video as a media in English learning has a positive effect and can improve cognitive abilities, learning performances, developing interests, motivation and better understanding of the concept of the lesson being taught.